To Determine the Efficacy of Polyethylene Glycol in the Treatment of Pediatric Constipation (Medical Forum Monthly, 2024)
Objective: To assess the efficacy of polyethylene glycol (PEG) in treating pediatric constipation and provide local statistics for improved clinical decision-making and recommendations on future treatment strategies.Study Design: Randomized Controlled Trial(RCT)Place and Duration of Study: This study was conducted at the department of Women and Children Hospital from January 2023 to January 2024.Methods: A descriptive case series was conducted with 146 pediatric patients over six months. Children aged 4 years and older underwent clinical examinations, including abdominal and rectal assessments. Polyethylene glycol (PEG 3350) was administered at 1.5 g/kg/day as a single dose for four weeks. Treatment efficacy was evaluated at the end of the 4th week.Results: The mean age of the patients was 8 years (SD ± 6.34). Of the 146 participants, 58% were male, and 42% were female. Polyethylene glycol was effective in 72% of the patients. The p-value for the efficacy of treatment was statistically significant (<0.05), indicating that PEG was an effective treatment option for most patients.Conclusion: Polyethylene glycol demonstrated significant efficacy (72%) in managing pediatric constipation. The findings highlight its effectiveness as a primary treatment option. Future research should focus on long-term outcomes and alternative dosages for children who do not respond to initial treatment.